2006
DOI: 10.1007/s11205-006-9030-1
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and psychological well-being

Abstract: sleep, psychological well-being, depression, anxiety,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 38 publications
7
100
2
4
Order By: Relevance
“…74 Our results also suggest that higher levels of self-reported physical and spiritual well-being are associated with decreased levels of emotional exhaustion. If this association is real, interventions to help nurses expand their repertoire of activities to support their physical well-being (eg, exercise, [75][76][77] healthy eating, 77,78 and adequate sleep 79 ) may help reduce burnout and mitigate moral distress. In one investigation, 77 even 15 minutes of additional exercise improved the study participants' health.…”
Section: Discussionmentioning
confidence: 99%
“…74 Our results also suggest that higher levels of self-reported physical and spiritual well-being are associated with decreased levels of emotional exhaustion. If this association is real, interventions to help nurses expand their repertoire of activities to support their physical well-being (eg, exercise, [75][76][77] healthy eating, 77,78 and adequate sleep 79 ) may help reduce burnout and mitigate moral distress. In one investigation, 77 even 15 minutes of additional exercise improved the study participants' health.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of anxiety and insomnia to illness is well known, however, the result of the study is an indication that these conditions have no influence on their state of being independent. On the other hand, Hamilton, et al, (2007) [15] reported that symptoms of insomnia were found to have a significant relationship with both psychological and subjective well-being but a stronger relationship to subjective wellbeing. These data suggest that insomnia symptoms have a stronger relationship to enjoying life than to the perception that one has a meaningful life.…”
Section: Specific Component Of Mental Health and Psychological Well-bmentioning
confidence: 99%
“…Сон влияет на уровень физического развития, поведение и эмоциональное состояние, когнитивное функционирование и способность к обучению, особенно у растущего организма. Полно-ценность сна определяет общий уровень здоровья и качество жизни, измеряемые в показателях соци-ального, психического, эмоционального и физиче-ского благополучия [23,27]. Издавна существовали несколько гипотез о назначении фаз сна.…”
Section: сон: физиологические аспекты и особенности цикла «сон -бодрсunclassified
“…Следует отметить, что с ожирением и нарушения-ми сна тесно связаны психологические проблемы [23]. Связь между сном и депрессией ранее была показана у лиц, не страдающих ожирением [20].…”
Section: нарушения сна ожирение и психокогнитивная дисфункцияunclassified